Uso de preparações caseiras de plantas medicinais utilizadas no tratamento de doenças infecciosas - Bastos, Gisele Medeiros (2007)
Most of the people in developing countries use plants or herbal preparations in their basic health care. The lack of information about the possible risks and benefits in the use of medicinal plants is one of the main factors that contribute with herbs automedication. Many plants used in the popular medicine have proved antimicrobial properties; however, several factors for example, incorrect preparation of the plants, can interfere in the efficiency of the treatment. The aim of this study was to assess-ment the use of domestic preparations of medicinal plants by the families of children who study in the Centre of Children Education Aprisco, in Fortaleza. The families that participated of the study answered a questionnaire that allowed knowing the most used medicinal plants by this population, as well as its therapeutic indications, forms of use, parts of the plant used, and other ones. At a second moment, an in vitro ex-perimental study analysed the antimicrobial potential of the domestic preparations of the medicinal plants quoted during the interviews. The data were inserted and ana-lysed in the Microsoftware package Office Excel and in the statistical program Epi Info 3.3.2. Forty one families were interviewed, of which 97,6 % affirmed to use the medicinal plants like therapeutic option in the treatment of diseases. In 39 question-naires were quoted 97 domestic preparations of plants, with an average of 2,5 ± 1,6 preparations. Of this total (97), 71,1 % was used to respiratory and digestive prob-lems. Furthermore, the most used part of the plant was the leaf (60 %) and the de-coction was the main form of the use (59,8 %). Thirty two plants species were used in the preparations, of which the eucalyptus (Eucalyptus citriodora) had the highest fre-quency (11,9 %). From the forty five samples that was submited to the antimicrobial activity in vitro, 55,6 % (25 samples) showed inhibitory activity on the growth at least one of the microorganisms used in the test. Many of the plants that have antimicro-bial properties and that were quoted by the families interviewed, had their activity al-tered in accordance with the form that they were prepared. It was also observed the use of plants for health care that present in their composition toxic substances. The results of this study suggest that the forms of preparation and use of the plants can interfere on the presence or absence of the farmacology activity that is attributed for the plants. Therefore, it’s in the pharmacist’s hands, who can contribute with his knowledge, to promote the efficient, safe and rational use of the medicinal plants.